Minimization of mean square error for improved euler elliptic curve secure hash cryptography for textual data. Issue 6 (18th August 2017) - Mehta, Ekta; Solanki, Arun
Abstract: Elliptic Curve Cryptography is a currently pursued research topic to be used in the security system that enhances the performance of unexpected character at the time of decryption process. In comparison with the traditional cryptosystems, for example, the RSA i.e. Rivest Shamir Algorithm, an Elliptic Curve Cryptography (ECC) provides equal security with the use of smaller key sizes, which produces faster computations, power usage is lowered, as well as memory usage and bandwidth variations are less. In the proposed technique, Euler based Elliptic curve secure hash (ECSH-Euler) that overcome the problem of Euler Totient function based on fixed key for prime number coefficient corresponding matrix based on the plain text's ASCII values is proposed. Values in a pair are defined as input for the hash key in the ECC. This new technique removes the need for the costly operation where mapping is done and the where there exists a requirement of sharing the same ASCII matrix for both purposes that are encryption and decryption .Both, the lookup table that is common between the sender - receiver along with the equation provides more security due to the reason of producing a numerical solution to a problem of initial value. Thus in this, a comparison of existing ECC and ECSH-Euler is also shown that resulted in minimization of RMSE for our proposed technique, which is simulated in MATLAB-2014Ra tool.